Enhancing clinical recovery of bovine tropical theileriosis by use of antioxidant supportive therapy - KUMAR, ASHWANI; RAKHA, N K; VIRMANI, MEENAKSHI (The Indian Journal of Animal Sciences, 2016)
The present study was conducted to test the hypothesis that oxidative stress plays important role in pathogenesis of bovine tropical theileriosis and the oxidative stress may be mitigated by supportive therapy with anti-oxidants, hastening recovery process from diseased to normal status. Animals (20) clinically infected with bovine tropical theileriosis were divided into 2 groups of 10 animals each and 6 healthy (uninfected) animals were kept as control. Group A animals were treated with buparvaquone alone and group B animals were treated with buparvaquone along with ascorbic acid. These groups were further subdivided into subgroups A1, A2 and B1, B2 as per schizont and piroplasm stage of disease. All infected animals harboured either schizonts or piroplasms of T. annulata and showed high grade fever, anaemia, inappetence and enlarged superficial lymph nodes. Significant decrease in level of haemoglobin (Hb), packed cell volume (PCV), total erythrocytes count (TEC) and total leucocytes count (TLC) along with lymphocytopenia was observed in infected animals. Treatment of diseased animals with theilericidal drug (buparvaquone) led to disappearance of the clinical symptoms, elimination of parasite population and recovery in hematocrit values. However, recovery was significantly better in animals of group B as compared to group A. Oxidative stress was detected by measuring level of lipid peroxidation [malondialdehyde (MDA) concentration] and antioxidant enzymes viz. glutathione peroxidase (GPx) and superoxide dismutase (SOD) in plasma of infected animals before and after treatment. There was development of oxidative stress in the animals as confirmed by significant increase in plasma MDA, increased activity of GPx and SOD enzymes as compared to corresponding values estimated in plasma of healthy animals. Ascorbic acid was found better in treating clinical cases of bovine tropical theileriosis. However, addition of antioxidant (ascorbic acid) further hastened the recovery process.